A Ten‐Year Molecular Survey on Parvoviruses Infecting Carnivores in Bulgaria. Issue 4 (8th November 2014) - Filipov, C.; Desario, C.; Patouchas, O.; Eftimov, P.; Gruichev, G.; Manov, V.; Filipov, G.; Buonavoglia, C.; Decaro, N.
Summary: Parvoviruses represent the most important infectious agents that are responsible for severe to fatal disease in carnivores. This study reports the results of a 10‐year molecular survey conducted on carnivores in Bulgaria ( n  =   344), including 262 dogs and 19 cats with gastroenteritis, and 57 hunted wild carnivores. Real‐time polymerase chain reaction (qPCR), followed by virus characterization by minor groove binder (MGB) probe assays, detected 216 parvovirus positive dogs with a predominance of canine parvovirus type 2a (CPV‐2a, 79.17%) over CPV‐2b (18.52%) and CPV‐2c (2.31%). Rottweilers and German shepherds were the most frequent breeds among CPV‐positive pedigree dogs ( n  =   96). Eighteen cats were found to shed parvoviruses in their faeces, with most strains being characterized as FPLV ( n  =   17), although a single specimen tested positive for CPV‐2a. Only two wild carnivores were parvovirus positive, a wolf ( Canis lupus ) and a red fox ( Vulpes vulpes ), both being infected by CPV‐2a strains.